CRIMINAL RESPONSIBILITY IN GOVERNMENT PROCUREMENT OF GOODS AND SERVICES IN OFFICIAL AND PERSONAL CONTEXTS - Guntur Rambey; Surya Perdana; Muhammad Arifin (Faculty of Law, Universitas Pekalongan, 2023)
Procurement of goods and services is a very urgent need in a developing country, the need for goods and services certainly requires quite large funds to obtain them. Service Users (in this case the Government) certainly expect good quality goods and services with the smallest amount of capital, while Service Providers (in this case the Contractor) will expect large profits, these two interests will attract each other. other. Procurement of goods and services is increasingly chaotic due to the lack of legal regulations in the form of laws, while the legal regulations used so far are only at the level of Presidential Decrees (Kepres) and Presidential Regulations. When talking about Procurement of Goods and Services, it includes several legal provisions, namely Civil law, if it concerns contracts, of course the legal consequence is a Civil lawsuit, if it concerns administrative decisions then it will be resolved through the Administrative Court, then if there is an allegation of a criminal act of misappropriation of State finances it will be resolved through criminal law, however, the specific legal rules for criminal liability for perpetrators of procurement of goods and services still use the provisions of general criminal law and the Corruption Crime Law. The method used in this research uses normative research. Normative legal research methods are research that positions law as a building system of norms.